The Role of Libraries in Harnessing Indigenous Knowledge in Ghana - Alemna, A.A. (Ghana Library Journal, 2004)
This paper begins with various definitions of Indigenous Knowledge (I.K) and goes on to consider the potential roles of three categories of libraries in Ghana - Special, Public and University, in harnessing IK. The conclusion is that due to various constraints, these libraries are not doing enough in the area of IK, despite its major value as an information source.